Mempelajari Aktivitas Antioksidan Sinamaldehid dan Karvakrol dengan Substitusi Gugus NO2 dan CH3 Berdasarkan Metode Density Functional Theory (DFT) - Azuxetullatif .; Fatridha Yansen (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2026)
Free radical are then main cause of tissue damage in the human body. Excess free radicals will result in various diseases such as cancer, diabetes, and heart disease. To minimize the excess of free radicals in the human body, antioxidant compounds are needed. One of the natural antioxidant compounds is terpenoid. Terpenoid derivatives that are known to have high antioxidant properties are Cinnamaldehyde and carvacrol. This study aims to predict the antioxidant activity of cinnamaldehyde and carvacrol compounds substituted with NO2 and CH3 groups theoretically, using the Density Functional Theory (DFT). The results of the study showed that cinnamaldehyde and carvacrol compounds substituted with the NO2 group had better antioxidant activity than those substituted with the CH3 group by considering the results of small BDE values, small SET-PT, small PA, small ETE, and small ?Egap